1972
DOI: 10.1111/j.1476-5381.1972.tb08117.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of central adrenoceptors for control of cardiovascular function

Abstract: Summary1. In dogs anaesthetized with pentobarbitone sodium, bradycardia with hypotension occurred on intracerebroventricular (i.c.v.) injection of noradrenaline (50-200 ,ug) or phenylephrine (100-400 ug), but tachycardia with hypotension occurred on i.c.v. injection of isoprenaline (100-200 ,ug). 2. These cardiovascular responses were central effects, and from the results obtained after bilateral vagotomy, removal of both stellate ganglia and transection of the upper cervical cord, it was evident that the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
2

Year Published

1974
1974
1987
1987

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 16 publications
1
15
0
2
Order By: Relevance
“…However, the number of neurons which elicited excitatory responses to NE was larger in ATn sensitive neurons than in AT], non-sensitive neurons, as determined statistically. Considerable evidence has accumulated for the hypotensive action of a adrenergic stimulants and Q-adrenergic blockers as the result of central mechanisms (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of neurons which elicited excitatory responses to NE was larger in ATn sensitive neurons than in AT], non-sensitive neurons, as determined statistically. Considerable evidence has accumulated for the hypotensive action of a adrenergic stimulants and Q-adrenergic blockers as the result of central mechanisms (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Intracerebroventricular (i.c.v. ) injections of noradrenaline or adrenaline evoked hypotension and bradycardia in cats and dogs (Nashold, Mannarino & Wunderlich, 1962;Bhargava, Misra & Tangri, 1972). On the other hand, both excitatory and inhibitory cardiovascular responses, blocked by propranolol and phentolamine respectively, were reported with i.c.v.…”
Section: Introductionmentioning
confidence: 99%
“…In this, the situation resembles that reported for noradrenaline by Cowell & Davey (1968) where, however, central and peripheral actions opposed each other whereas those of isoprenaline are similar. Gagnon & Melville (1967) and Bhargava et al (1972) have shown that intracerebroventricular isoprenaline stimulated central,-adrenoceptors since,-adrenoceptor blocking agents injected by the same route blocked the effects. It may be presumed that the central components of the actions of isoprenaline in the mouse are similarly mediated, though leakage of ,B-adrenoceptor blocking agents after intracerebroventricular injection in mice would preclude a decisive experiment along these lines, since the circulating agent could affect a tachycardia of central origin by blocking peripherally.…”
Section: Discussionmentioning
confidence: 99%
“…From this evidence it was suggested that sympathetic receptors exist in central regions paralleling those postulated in the periphery by Ahlquist (1948). Bhargava, Mishra & Tangri (1972) have shown these effects of intracerebroventricular isoprenaline to be central in origin in anaesthetized dogs by experiments in which bilateral removal of the stellate ganglion or transection of the upper spinal cord was carried out. Using conscious cats Day & Roach (1972) showed that intracerebroventricular isoprenaline produced tachycardia and hypertension, the latter being due to an increased systolic pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation